Attitudes of students of a health sciences university towards the extension of smoke-free policies at the university campuses of Barcelona (Spain) - Cristina Martínez; Carlos Méndez; María Sánchez; José María Martínez-Sánchez (Elsevier, 2017)
Objective: To assess attitudes towards the extension of outdoor smoke-free areas on university campuses. Methods: Cross-sectional study (n = 384) conducted using a questionnaire administered to medical and nursing students in Barcelona in 2014. Information was obtained pertaining to support for indoor and outdoor smoking bans on university campuses, and the importance of acting as role models. Logistic regression analyses were performed to examine agreement. Results: Most of the students agreed on the importance of health professionals and students as role models (74.9% and 64.1%, respectively) although there were statistically significant differences by smoking status and age. 90% of students reported exposure to smoke on campus. Students expressed strong support for indoor smoke-free policies (97.9%). However, only 39.3% of participants supported regulation of outdoor smoking for university campuses. Non-smokers (OR = 12.315; 95% CI: 5.377-28.204) and students ≥22 years old (OR = 3.001; 95% CI: 1.439-6.257) were the strongest supporters. Conclusions: The students supported indoor smoke-free policies for universities. However, support for extending smoke-free regulations to outdoor areas of university campuses was limited. It is necessary to educate students about tobacco control and emphasise their importance as role models before extending outdoor smoke-free legislation at university campuses.